The Application Of The Principle Of Judges Freedom On SEMA Number 2 Of 2023 - Tri Hidayati; Ajeng Hijriatul Aulia; Risna Wendy Wiraganti (Al-Adl : Jurnal Hukum, 2024)
This study aims to determine the position of the Supreme Court Circular Letter in the judicial system in Indonesia and the binding force of Supreme Court Circular Letter Number 2 of 2023 concerning Guidelines for Judges in Handling Applications for Registration of Marriages of Different Religions (Supreme Court Circular Letter number 2 of 2023) on the freedom of District Court judges in handling applications for registration of marriages of different religions in Indonesia. This research is normative legal research, using statutory and conceptual approaches and analyzed using content analysis techniques. The findings are that the Supreme Court Circular Letter does not have the status of a binding legal norm but has a moral force that binds judges in the judicial environment. Decisions in Supreme Court Circulars often reflect in-depth legal interpretation and the experience of judicial practitioners. Supreme Court Circular Letter No. 2 of 2023 aims to strengthen and direct the principle of judges' independence towards the achievement of better justice. The implementation of Supreme Court Circular Number 2 of 2023 will depend on the awareness and commitment of judges, as well as the full support of the judiciary and other relevant stakeholders.